Firm-specific Human Capital as a Contract Determining Factor – a Reason for Internal Bilateral Interdependence between the Employer and the Employee (Economic and Political Thought, 2018)
As a result of its own strategy, gradual development, vertical integration orother factors, a firm may experience employing a worker with some firm-specifichuman capital. This situation implies a kind of interdependence between theemployer and the employee whose knowledge and abilities can be perceived asa specific asset. Both parties become strongly interdependent: the employer hasto rely on the employee and, on the other hand, the employee cannot change hisworkplace easily. The presented relations are compared to a bilateral monopolysituation in order to examine the possibility of using analogous research tools.This paper identifies difficulties accompanying the functioning of the firm, whenthe core business is based on firm-specific human capital and contains solutionsreferring to transaction costs economics and the agency theory.
Keywords: transaction costs economics, vertical integration, human capital, specific assets, interdependence, efficiency wages, ownership, agency theory